2020
DOI: 10.12928/telkomnika.v18i3.14885
|View full text |Cite
|
Sign up to set email alerts
|

Single camera depth control in micro class ROV

Abstract: Navigation is one of the main challenges in an underwater vehicle. To measure and sustain the depth in the micro class remotely operated vehicle (ROV) robot is one of the main demands in the underwater robot competition. There are many sensors that can be used to measure the depth; one of the sensors is using a single camera sensor. In this works, camera-based depth control is developed and evaluated for micro class ROV, namely as fitoplankton SAS ROV. Fitoplankton SAS ROV is a micro ROV prototype with six thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These two main specialties of OCC are sufficient to deduce that OCC is a research-worthy topic and a futuristic technology [6]. Figure 1 shows the basic working principle of OCC (Figure 1 Even though the invention of omnidirectional wheel such as omniwheel [7] and Mecanum wheel [8] happened over half century ago, but the proposal and development of OCC-related research has only been started since around two decades ago. They can be classified to either omnidirectional conveyor (OC), cellular conveyor (CC) or OCC.…”
Section: Introductionmentioning
confidence: 99%
“…These two main specialties of OCC are sufficient to deduce that OCC is a research-worthy topic and a futuristic technology [6]. Figure 1 shows the basic working principle of OCC (Figure 1 Even though the invention of omnidirectional wheel such as omniwheel [7] and Mecanum wheel [8] happened over half century ago, but the proposal and development of OCC-related research has only been started since around two decades ago. They can be classified to either omnidirectional conveyor (OC), cellular conveyor (CC) or OCC.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous underwater vehicle (AUV) considered one of the several studies that have discussed during the last decades due to its purposes and applications in different fields such as militaries, exploring the ocean submarines, oil and gas fields. In the literature, numerous controllers are presented for control the AUV the authors suggested different techniques to solve or handle the AUV problems like [1][2][3][4][5]. During the movement of AUV towards the vertical location, the sensors used in the AUV control model can add a considerable amount of noise which leads to change the tolerance and stability of the system as a result of that movement of AUV become unsettled.…”
Section: Introductionmentioning
confidence: 99%